1997
DOI: 10.1074/jbc.272.14.9182
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the COQ5 Gene from Saccharomyces cerevisiae EVIDENCE FOR A C-METHYLTRANSFERASE IN UBIQUINONE BIOSYNTHESIS

Abstract: Ubiquinone (coenzyme Q or Q) is a lipophilic metabolite that functions in the electron transport chain in the plasma membrane of prokaryotes and in the inner mitochondrial membrane of eukaryotes. Q-deficient mutants of Saccharomyces cerevisiae fall into eight complementation groups (coq1-coq8). Yeast mutants from the coq5 complementation group lack Q and as a result are respiration-defective and fail to grow on nonfermentable carbon sources. A nuclear gene, designated COQ5 was isolated from a yeast genomic lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 89 publications
(83 citation statements)
references
References 54 publications
1
81
1
Order By: Relevance
“…Since ubiquinone biosynthetic enzymes are localized to the mitochondria of S. cerevisiae (4,11,27), it has been suggested that ubiquinone biosynthesis occurs in the mitochondria. To assess the case for homologous enzymes from S. pombe, the localization of S. pombe Ppt1 was examined by Ppt1-green fluorescent protein FIG.…”
Section: Resultsmentioning
confidence: 99%
“…Since ubiquinone biosynthetic enzymes are localized to the mitochondria of S. cerevisiae (4,11,27), it has been suggested that ubiquinone biosynthesis occurs in the mitochondria. To assess the case for homologous enzymes from S. pombe, the localization of S. pombe Ppt1 was examined by Ppt1-green fluorescent protein FIG.…”
Section: Resultsmentioning
confidence: 99%
“…Medium was prepared as described (31) and included YPD (2% glucose, 1% yeast extract, 2% peptone), YPgal (2% galactose, 0.1% glucose, 1% yeast extract, 2% peptone), and YPG (3% glycerol, 1% yeast extract, 2% peptone). Synthetic dextrose/minimal medium was prepared as described (32) and consisted of all components (SDcomplete) or all components minus histidine (SDϪHis). Drop out dextrose medium (DOD) was prepared as described (33), except that galactose was replaced with 2% dextrose.…”
Section: Methodsmentioning
confidence: 99%
“…Growth media for yeast were prepared as described (34) and included YPD (1% yeast extract, 2% peptone, 2% dextrose), YPE (1% yeast extract, 2% peptone, 2% ethanol), YPGal (1% yeast extract, 2% peptone, 2% galactose), YPG (1% yeast extract, 2% peptone, 3% glycerol), SDC (0.18% yeast nitrogen base without amino acids, 2% dextrose, 0.14% NaH 2 PO 4 , 0.5% (NH 4 ) 2 SO 4 , complete amino acid supplement), SD-Leu (SDC minus leucine), and SD-Ura (SDC minus uracil). The complete supplement was modified so that the final concentration of each component was as described (23). Semisynthetic lactate media was prepared as described (35).…”
Section: Methodsmentioning
confidence: 99%
“…Coq3p is located in the mitochondrial matrix, peripherally associated with the inner membrane and catalyzes both O-methylation steps in Q biosynthesis (22). Coq5p functions as a C-methyltransferase in the mitochondria (23,24). Coq6p is likely to function as a flavin-dependent monooxygenase, adding one or more of the ring oxygens (20).…”
Section: Ubiquinone (Coenzyme Q or Q)mentioning
confidence: 99%